P578Age-dependent transcriptomic changes in the rat heart. Implications for cardiac arrhythmogenesis. (15th July 2014) - Scridon, A; Fouilloux-Meugnier, E; Loizon, E; Rome, S; Julien, C; Barres, C; Chevalier, P
Abstract: Purpose: Aging is associated with significantly increased prevalence of cardiac arrhythmias, but transcriptional events that underlie this process remain to be established. To gain deeper insight into molecular mechanisms of aging-related cardiac arrhythmias, we performed mRNA expression analysis comparing atrial and ventricular myocardium from healthy Wistar-Kyoto (WKY) rats of different ages. Methods: Atrial and ventricular sampling was performed in 3 groups (n=4 each) of young (14-week-old), adult (25-week-old), and aging (47-week-old) WKY rats. mRNA expressions of 89 genes involved in cardiac arrhythmogenicity were investigated using TaqMan Low Density Array analysis. Results: Of the 89 studied genes, 40 and 64 genes presented steady atrial and ventricular expressions, respectively. All genes differentially expressed within the atria of WKY rats were up-regulated with advancing age, mainly the genes encoding for various K+, Ca2+, Na+ channels, and type 6 collagen. Atrial expression levels of 19 genes were positively correlated with age. Ventricular transcriptomic analysis revealed a balance between up-regulated and down-regulated genes encoding for the same ion channels. Conclusions: Our results indicate the induction of an up-regulation transcriptional response in atrial but not ventricular myocytes with advancing age, suggesting that the two chambers undergo different molecular remodeling programs. Aging atria displayed a transcriptomic profile consistent with higher propensity to arrhythmias, including up-regulation of genes encoding for If, ICa-L, ICa-T, INa, outward K + currents, and collagen, while ventricular transcriptome did not seem to be significantly altered by aging. These observations could explain the higher propensity to atrial than ventricular arrhythmias in the elderly.